Mediation in Belgian administrative practice, with special focus on municipal administrative sanctions and urban planning - Veny, Ludo (Mednarodna revija za javno upravo, 2014)
Given Belgian legal doctrine, the rise of mediation in other legal disciplines, and the influence of the EU, the call for mediation in administrative practice is increasing in Belgium. The proposed framework for ADR in the legal doctrine at the beginning of this century was the start of the increasing use of mediation in Belgian administrative law. This contribution is a study of these new forms of mediation as they occur in Belgium in the year 2014. On the basis of two examples (mediation in municipal administrative sanctions and urban planning), administrative mediation and the associated problems are outlined.
Keywords: alternative dispute resolution; alternativno reševanje sporov; Belgija; Belgium; mediacija; mediation; municipal administrative sanctions; občinske upravne sankcije; upravno pravo; urban planning; urbanistično načrtovanje